RELATIONSHIP OF GLYCAEMIA AND TRIGLYCERIDES WITH BMI IN DIABETIC PATIENTS - Parvez, Arshad; ullah, Ihsan; Rafiq, Ahmad; Ahmad, Nisar; Khan, Ejaz Hassan (Journal of Ayub Medical College Abbottabad, 2010)
Background: Diabetes mellitus (DM) is a metabolic disorder characterised by chronic hyperglycaemia with disturbances in carbohydrate, fat and protein metabolism arising from defect in insulin secretion or action or both. The clinical guidelines recommend measurement of BMI as vital signs for evaluating the obese and diabetic patients. Methods: This study was carried out on 160 diabetics, which were divided on the basis of BMI into obese (120) and non-obese (40) diabetics from Peshawar district. All patients had their triglycerides and glucose checked after over night fast. Results: The serum triglyceride in diabetics having BMI >30 (obese) was increased as compared to patients having BMI <30 (non-obese). The comparison of serum glucose level in obese diabetics was found to be significantly raised as compared to non-obese diabetics. Conclusions and Recommendations: It was concluded that dyslipidemia is common in all diabetics. The abnormal triglyceride level can improve with good glycaemic control, but do not reach the normal state. Good glycaemic control, Reducing BMI, periodic checkups of lipids and blood glucose are recommended for all diabetics in order to avoid complications. Keywords: Triglyceride, BMI, obese, non-obese, type 2 diabetics